Dependence of reactions of the external respiratory system in athletes on the orientation of the training process - S. M. Kanyhina; M. S. Potapenko; L. O. Kurilets (Patologìâ)
Issues of improving the functional training (different orientation of the training process) of athletes due the development of the respiratory system, including the respiratory system, as well as increasing the body's resistance to hypoxic stress remain extremely relevant at the present stage of sport development.